Pemuda Cerdas Digital: Pelatihan Desain Grafis dengan Canva di SMA Imelda Medan - Ika Yusnita Sari; Elvika Rahmi; Khairunnisa Khairunnisa; Maristella J Lumbanbantu; Astrida N Marpaung (CV. Devi Tara Innovations, 2024)
The program titled